2016
DOI: 10.1105/tpc.16.00249
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Transit: Long-Distance Trafficking and Phloem Unloading of Protein Signals in Arabidopsis Homografts

Abstract: In addition to moving sugars and nutrients, the phloem transports many macromolecules. While grafting and aphid stylectomy experiments have identified many macromolecules that move in the phloem, the functional significance of phloem transport of these remains unclear. To gain insight into protein trafficking, we micrografted Arabidopsis thaliana scions expressing GFP-tagged chloroplast transit peptides under the 35S promoter onto nontransgenic rootstocks. We found that plastids in the root tip became fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 51 publications
4
97
0
Order By: Relevance
“…This question was experimentally addressed in the recent work of Paultre et al (2016). The authors used Arabidopsis micrografts to test whether transit peptides tagged with GFP variants are phloem mobile.…”
Section: Mobility Of Macromolecules Formed In Companion Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This question was experimentally addressed in the recent work of Paultre et al (2016). The authors used Arabidopsis micrografts to test whether transit peptides tagged with GFP variants are phloem mobile.…”
Section: Mobility Of Macromolecules Formed In Companion Cellsmentioning
confidence: 99%
“…Using Arabidopsis thaliana micrografts, a recent Breakthrough Report by Paultre et al (2016) showed scion-expressed, fluorescent protein-tagged signal peptides in the root unloading zone of wild-type rootstocks. This finding indicates that tagged proteins formed in the companion cells entered neighboring sieve elements through the pore-plasmodesma units (PPUs) and were swept along with the phloem stream across the graft union into the root.…”
mentioning
confidence: 99%
“…It is more likely that the high native sizeexclusion limit of PPUs is the key factor that determines whether a protein will, or will not, enter the translocation stream. In the case of CC proteins (Paultre et al, 2016) and mobile mRNAs (Calderwood et al, 2016), simple abundance and size may determine the likelihood of macromolecular movement from CC to SE, the size-exclusion limit of PPUs determining the upper molecular cutoff. Intriguingly, almost all the examples of native, phloemmobile macromolecules cited by Schulz (PP2, FT, and CmPP16) fit these criteria.…”
mentioning
confidence: 99%
“…The possibility that protein overexpression from strong promoters may induce the translocation of proteins was discussed by Paultre et al (2016), leading to their bioinformatic analysis of phloem exudate composition. However, these data are criticized by Schulz as unreliable since cutting the phloem may lead to pressure-induced surge artifacts, causing proteins to enter the translocation stream from the adjacent CCs.…”
mentioning
confidence: 99%
“…In a recent Breakthrough Report, Paultre et al (2016) address the movement of proteins through the phloem. They used a grafting system (see figure) where the protein or domain of interest is expressed from the 35S promoter as a fusion to GFP in the scion, which is then grafted onto a nontransgenic, wild-type rootstock.…”
mentioning
confidence: 99%